So you want to be in advertising - Caffrey, Ed (New York: Simon and Shuster, 1998)
Starting careers in the big city or out of town, a day in the life of an ad agency, account work: bussines skills, dialing with creative, media and research, how to study and preapare for a job in research and media. production, the portfolio, the end the pressures.
Incluye bibliografía
Keywords: Estudio; Publicidad